Changes in Stroke Rehabilitation during the Sars-Cov-2 Shutdown in Switzerland - Jeremia P. O. Held; Anne Schwarz; Johannes Pohl; Eva Thürlimann; Silvan Porrtmann; Meret Branscheidt; Madalina Fratian; Jannie van Duinen; Janne M. Veerbeek; Andreas R. Luft (Medical Journals Sweden, 2022)
Introduction: Many stroke survivors require continuous outpatient rehabilitation therapy to maintain or improve their neurological functioning, independence, and quality of life. In Switzerland and many other countries, the shutdown to contain SARS-CoV-2 infections led to mobility restrictions and a decrease in therapy delivery. This study investigated the impact of the COVID-19 shutdown on stroke survivors' access to therapy, physical activity, functioning and mood. Methods: A prospective observational cohort study in stroke subjects. At 4 time-points (before, during, after the shutdown, and at 3-month follow-up), the amount of therapy, physical activities, motor function, anxiety, and depression were assessed. Results: Thirty-six community-dwelling stroke subjects (median 70 years of age, 10 months post-stroke) were enrolled. Therapy reductions related to the shutdown were reported in 72% of subjects. This decrease was associated with significantly extended sedentary time and minimal deterioration in physical activity during the shutdown. Both parameters improved between reopening and 3-month follow-up. Depressive symptoms increased slightly during the observation period. Patients more frequently reported on self-directed training during shutdown. Conclusion: The COVID-19 shutdown had measurable immediate, but no persistent, effects on post-stroke outcomes, except for depression. Importantly, a 2-month reduction in therapy may trigger improvements when therapy is fully re-initiated thereafter. Lay abstract In Switzerland and in many other countries, the shutdown to contain SARS-CoV-2 infections led to a reduced mobility and a reduction in therapy delivery. The impact of the shutdown on stroke survivors' access to therapy, physical functioning, and mood was investigated in an observational study. Before, during, and after shutdown, the amount of therapy, motor functioning, and anxiety and depression were collected. Thirty-six community dwelling subjects were enrolled at a median of 10 months post-stroke. Therapy reductions related to the shutdown were reported in 72% of subjects. This was associated with an increased sedentary time and minimal deterioration in motor functioning, which improved after reopening. Depression increased slightly during the observation. Patients more frequently reported on self-directed training during shutdown. The COVID-19 shutdown had measurable immediate, but no persistent, effects on post-stroke outcomes, except depression. In fact, a 2-month reduction in therapy may trigger improvements when therapy is fully re-initiated thereafter.